Comparison between loquat cultivars grown under screen and regular fields - Soler E.; Juan N. (First international symposium on loquat, 2003)
Culture of loquat species under screen has increased from the 80s until now in the Marina Baixa county. Culture of loquat under screen began as a protection from climate agents, and especially from wind. However other characteristics related to yield and fruit quality improved when growing in these conditions. In this study a comparison of different loquat varieties, grown under screen and in regular fields, is shown. Data were provided by growers from the Callosa Growing Association corresponding to the 2000-2001 crop year. All plots received the same standard cultural practices. Results showed that culture of loquat under screen, besides protecting the fruit from bad weather, resulted in increased fruit size, keeping the rest of factors at the same level. On the other hand, results suggested that those trees grown under screen could need less fruit thinning, without losing fruit quality. These results must be confirmed during the next crop years.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)